2017
DOI: 10.1007/s10803-017-3402-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Validity of a Quality of Life Measure for Autistic People

Abstract: Accurate measurement of quality of life (QoL) is important for evaluation of autism services and trials of interventions. We undertook psychometric validation of the World Health Organisation measure—WHOQoL-BREF, examined construct validity of the WHO Disabilities module and developed nine additional autism-specific items (ASQoL) from extensive consultation with the autism community. The sample of 309 autistic people was recruited from the Adult Autism Spectrum Cohort-UK. The WHOQoL-BREF had good psychometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
173
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(180 citation statements)
references
References 55 publications
(65 reference statements)
5
173
0
2
Order By: Relevance
“…The large sample gave power to undertake analyses by age and gender. A robust measure of QoL is a strength, increasing the validity of the analysis; furthermore, the WHOQoL‐BREF has been further validated as a QoL measure for the autism population [McConachie et al, ] which strengthens the present findings.…”
Section: Discussionsupporting
confidence: 72%
“…The large sample gave power to undertake analyses by age and gender. A robust measure of QoL is a strength, increasing the validity of the analysis; furthermore, the WHOQoL‐BREF has been further validated as a QoL measure for the autism population [McConachie et al, ] which strengthens the present findings.…”
Section: Discussionsupporting
confidence: 72%
“…For example, McConachie et al examined the construct validity of the World Health Organization Quality of Life Measure (the WHOQoL-BREF) and developed nine additional autism-specific items based on consultations with groups of autistic adults in four countries. 36,37 While their methods may differ from ours, like us, they found that the existing measure did not fully capture the intended construct, so they worked with autistic adults to create additional items. Similarly, Rodgers et al 65 consulted with autistic adults to adapt an anxiety scale to be more accessible to this population.…”
Section: Discussionmentioning
confidence: 77%
“…For example, the wide range of scores regarding QoL in some subgroups suggest that there might be other predictors, which could result in another informative subgroup split. Moreover, recent studies have highlighted the importance of validating existing measures for outcome in the autism population [McConachie et al, ; Ayres et al, ; Cottenceau et al, ] so that we can make sure study results inform us on appropriate targets. Future research should replicate these findings in an independent sample, expanding the sample size and input features to establish a valid and clinically viable taxonomy for QoL in ASD.…”
Section: Discussionmentioning
confidence: 99%